2016
DOI: 10.1101/lm.039578.115
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of miR-132/-212 impairs memory and alters the hippocampal transcriptome

Abstract: miR-132 and miR-212 are structurally related microRNAs that have been found to exert powerful modulatory effects within the central nervous system (CNS). Notably, these microRNAs are tandomly processed from the same noncoding transcript, and share a common seed sequence: thus it has been difficult to assess the distinct contribution of each microRNA to gene expression within the CNS. Here, we employed a combination of conditional knockout and transgenic mouse models to examine the contribution of the miR-132/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 99 publications
(112 reference statements)
4
84
0
Order By: Relevance
“…Moreover, miR‐128‐3p has been shown to govern motor activity by suppressing the expression of various ion channels and mitogen‐activated protein kinase 1 (ERK2) signaling components and its overexpression attenuates motor abnormalities associated with Parkinson's‐like disease and seizures in mice . MMSE was negatively correlated with miR‐132‐3p, an miRNA that has been shown to regulate dopamine neuron differentiation by directly targeting Nurr1 mRNA and strongly linked to memory formation and retention . Furthermore, when PD patients were separated into normal/abnormal cognition, a statistically significant decrease in miR‐7‐5p expression levels was identified for total PD and SNCA A53T PD in patients with normal cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR‐128‐3p has been shown to govern motor activity by suppressing the expression of various ion channels and mitogen‐activated protein kinase 1 (ERK2) signaling components and its overexpression attenuates motor abnormalities associated with Parkinson's‐like disease and seizures in mice . MMSE was negatively correlated with miR‐132‐3p, an miRNA that has been shown to regulate dopamine neuron differentiation by directly targeting Nurr1 mRNA and strongly linked to memory formation and retention . Furthermore, when PD patients were separated into normal/abnormal cognition, a statistically significant decrease in miR‐7‐5p expression levels was identified for total PD and SNCA A53T PD in patients with normal cognition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-132 alters dendritic morphogenesis by activating the Rac1-PAK pathway (Impey et al, 2010, Wayman et al, 2008) and by regulating MeCP2 expression (Klein et al, 2007, Hansen et al, 2010). More recently, it has been shown that conditional knockout of miR-132/212 gene cluster impairs memory and promotes gross alterations in hippocampal transcriptional profile in mice (Hansen et al, 2016). …”
Section: Exercise and Circulating Mirnas (C-mirnas): The Link Betwmentioning
confidence: 99%
“…Moreover, data from different model organism show that noncoding RNAs such as microRNAs (miRNAs) are required for the regulation of plasticity‐involved genes. It is known that miRNA can repress the translation of target mRNAs or even lead to mRNA cleavage, thus reducing the amount of translated proteins . Given that neuronal communication happens at a much faster rate and is more dynamic than protein biosynthesis, miRNAs could help to adjust protein levels in this ever‐changing environment.…”
Section: Main Textmentioning
confidence: 99%
“…Given that neuronal communication happens at a much faster rate and is more dynamic than protein biosynthesis, miRNAs could help to adjust protein levels in this ever‐changing environment. However, miRNAs are also found at synapses, where they repress local synaptic translation until neuronal activity requires it . Some miRNAs seem to be directly expressed in response to CREB, highlighting their role in memory formation .…”
Section: Main Textmentioning
confidence: 99%